RESPONS PERTUMBUHAN DAN PRODUKSI BEBERAPA VARIETAS KEDELAI HITAM (Glycine max L.) BERDASARKAN UKURAN BIJI - Esra Lumbantobing Esra Lumbantobing; Emmy Harso Kardhinata; Rosmayati Rosmayati (Jurnal Agroekoteknologi, 2013)
Growth Respons and Production of Black Soybean Varieties (Glycine max L.) based on Seed Size.Use of yellow soybeans increases as the limited supply of black soybeans. Farmers to plant turnyellow soybean seed in higher production and larger in size than black soybean seed generally small.Size seed effect toward the utilization of soybean. The large seed size tends to be use as industrial rawmaterials while the size of small seeds use as a seed plant back. The aim of this research is toselection the use big size seed and small seed size from some varieties to increase production. Plantedon Community Land Pasar 1 Tanjung Sari, District Medan Selayang, Medan with a height of ± 25meter above sea level on Mei until August 2012. Randomized Block Design from that is varieties(Detam-1, Detam-2, Cikuray, and Mallika) and seed size (small seed size and big seed size) who thetreatment repeatedly 3 times. The parameters observased were plant height, number of branches onmain branches, flowering time, harvest time, number of pods per plant, number of pods containing,number of empty pods, production per plant, number of small size seed per plant, number of mediumsize seed per plant, and number of big size seed per plant. The research showed that the stastisticanalysis that varieties significant effects on plant height, number of branches on main branches,flowering time, harvest time, number of pods per plant, number of pods containing, number of smallsize seed per plant, number of medium size seed per plant, and number of big size seed per plant.